Peran Sekolah dalam Upaya Mencegah Kenakalan Remaja di SMP Negeri 1 Kota Semarang - Neneng Yovita Sari; Natal Kristiono (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the role of schools in preventing juvenile delinquency in public junior high schools in Semarang City and identify obstacles encountered in its implementation. The study used a qualitative approach with descriptive methods. The research subjects were determined purposively, including the principal, guidance and counseling teachers, homeroom teachers, and several students who were deemed to understand and be directly involved in efforts to prevent juvenile delinquency in schools. Data were collected through in-depth interviews, observations of school activities, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the most dominant forms of juvenile delinquency were violations of school rules, late arrivals, cell phone use during class, and conflicts between students. Preventive efforts undertaken by schools focused on consistent implementation of rules, strengthening character development, optimizing guidance and counseling services, and collaborating with parents. The main obstacles faced included differences in student character, the influence of the social environment, lack of family supervision, and limited time and educators' resources for intensive guidance. This study confirms that preventing juvenile delinquency in schools requires ongoing collaboration between schools, families, and the students' social environment.